Study of night calls in a family practice in Sri Lanka. - Jayawardene, LD (My University, 1987)
While the subject of 'night calls' has been dealt with from various angles in the developed countries, there has been no study of the subject for Sri Lanka 1,2. The practice of family medicine in Sri Lanka is basically different from that in developed countries, and there are inherent difficulties in transplanting these foreign findings to the local scene. This make a study done in this country very important.